FAKTOR-FAKTOR YANG MEMPENGARUHI PRAKTEK INCOME SMOOTHING PADA PERUSAHAAN LQ 45 YANG TERDAFTAR DI BEI TAHUN 2009-2014 - Fanani, Baihaqi; Pracistia, Geryta (PERMANA, 2014)
This study aims to know the effect of return on asset (ROA), net profit margin(NPM), company size and debt to equity ratio (DER) to income smoothing practice of the LQ 45 companies as gradually or partially. The statistic analysis used in this study are multilinear regression, partial signifancy test, simultant significancy test and determinant coefisient analysis. The conclusion of this study are ROA, company size and debt to equity ratio (DER) as partially have the significant effect to income smoothing practice of LQ 45 companies. But as gradually all of the independent variables have the effect to income smoothing practice of LQ 45 companies.The number of effect all of the independent variables have the effect to incomesmoothing practice of LQ 45 companies is 52,3%. Itâs explain that all the independent variables as gradually have the effect 52,3% to income smoothing practice and the other hand effected of other factors.Key words: return on assets, net profit margin, company size and debt to equity ratio.